2018
DOI: 10.9734/jammr/2018/45210
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Reported Symptoms of Musculoskeletal Disorders among Doctors at the University of Port-Harcourt Teaching Hospital, Nigeria

Abstract: Background: Musculoskeletal system disorders are potential sources of occupational Public Health concern with worldwide prevalence. These disorders arise as a result of exposure to hazards related to biomechanical overload which adversely affects the body's osteo-articular system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 14 publications
(26 reference statements)
2
2
0
Order By: Relevance
“…Other regions of the body also experienced musculoskeletal disorder symptoms among the respondents including the thoracic, abdominal, pelvic, perineal and limb regions. This finding is confirmed by an earlier study in the same locality that also reported high prevalence of musculoskeletal disorder symptoms among their study population [4]. Researchers in other parts of the world have also reported high prevalence of MSD symptoms among workers [16][17][18].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Other regions of the body also experienced musculoskeletal disorder symptoms among the respondents including the thoracic, abdominal, pelvic, perineal and limb regions. This finding is confirmed by an earlier study in the same locality that also reported high prevalence of musculoskeletal disorder symptoms among their study population [4]. Researchers in other parts of the world have also reported high prevalence of MSD symptoms among workers [16][17][18].…”
Section: Discussionsupporting
confidence: 86%
“…Regarding the association existing between prevalence of self-reported symptoms of musculoskeletal disorders and the work postures of our study respondents, we found statistically significant association between posture and pelvic/perineal pain. This finding is corroborated by the findings of other authors that identified working long periods in static positions could precipitate the occurrence of musculoskeletal disorder symptoms [4,24]. Other parts of the body were also reported to commonly experience MSD.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations